Patient outcomes in Anteromedial osteoarthritis patients over 80 years old undergoing Oxford Unicompartmental knee Arthroplasty in China - Cheng, Jingbo (BMC Musculoskelet Disord, 2020)
BACKGROUND: The use of Oxford Unicompartmental Knee Arthroplasty (UKA) has increased rapidly in both Western and Asian populations, with excellent functional outcomes and high patient satisfaction. While previous evidence regarding clinical outcomes and survival rates after Oxford UKA was based on studies in Western populations, the results may be different in Asian patients. The relevance of age for postoperative function after Oxford UKA also remains unclear. Hence, the aim of our study was to clarify the effectiveness and safety of Oxford UKA in Asian patients aged over 80 years. METHODS: A retrospective review was performed and included 195 patients (209 knees) who underwent an Oxford UKA between June 2015 and July 2018. We divided the patients into three groups by age: Group 1, 60–69 years; Group 2, 70–79 years; and Group 3, over 80 years. We used the Hospital for Special Surgery (HSS) score and Western Ontario and McMaster (WOMAC) Universities Osteoarthritis Index score to evaluate the general condition of the patients’ knees before surgery and at last follow-up. We also recorded perioperative and short-term complications. RESULT: Group 1 consisted of 60 patients (60 knees); Group 2, 70 patients (79 knees); and Group 3, 65 patients (70 knees). The mean follow-up was 21.34 ± 12.04, 22.08 ± 11.38, and 21.76 ± 10.20 months in groups 1, 2, and 3, respectively. At last follow-up, the patients in Group 3 showed lower function scores compared to groups 1 and 2 (P < 0.05), but the HSS scores and the WOMAC scores were significantly improved in all three groups. In terms of perioperative and other complications, the three age groups did not differ significantly. CONCLUSION: Oxford UKA is an effective and safe treatment for osteoarthritis, even in elderly patients in China. Elderly patients have lower knee function scores than younger patients. However, the knee joint pain of the elderly patients was relieved and function improved compared to the preoperative condition.